(untitled) (REMUNOM, 2024)
Geotourism is an aspect of tourism that focuses on valuing and understanding the natural resources (geological, geomorphological, paleontological, etc.) of a given location, and has gained prominence as an innovative way of exploring and promoting the geological and cultural heritage of a region. This work’s main objective was to identify the geodiversity of the Gitó and Tauá waterfalls, located in the municipality of Areia, in the state of Paraíba, as well to identify the geotouristic potential of the region and indicate strategies aimed at the geoconservation of relevant landscape heritage. To achieve these objectives, methodologies were adopted that included field research in addition to the use of geotechnology tools supported by the Geographic Information System (GIS), which played a crucial role in collecting and interpreting data, allowing the creation of a map geotouristic potential of the waterfalls. The results highlight that the Gitó and Tauá waterfalls have great potential for geotourism activities, in addition to offering opportunities for the development of ecotourism activities. Based on the data obtained, geoconservation strategies were proposed, including the creation of trails, the implementation of information signs about local geodiversity and the promotion of environmental education programs aimed at raising awareness about the importance of preserving geoenvironmental heritage. The study also analyzed the impact of geotechnologies on the development and promotion of geotourism, highlighting its contribution to the preservation of geoenvironmental heritage. Geotechnologies not only facilitated the documentation and monitoring of study areas, but also helped in the development of strategic proposals for the management and conservation of these areas. It is concluded that the integration of geotechnologies in the analysis and promotion of geotourism in the Gitó and Tauá waterfalls becomes essential for the valorization and conservation of geological heritage. The implementation of the suggested strategies can contribute, in part, to the sustainable development of the region, combining environmental conservation and tourism enhancement.